Experimental investigation on oil transport, heat transfer and distribution performances of R32/oil mixture in microchannel evaporators. (1st November 2022) - Zeng, Weijie; Zhang, Zhiting; Hu, Jinting; Gu, Bo; Tian, Zhen
Highlights: Oil retention and heat transfer of R32/PVE in two microchannel evaporators were measured. The internal volume occupied by the retained oil was measured up to 18.0%. The outlet header was the key component of oil retention. Oil influence on heat transfer is limited due to struggle of inhibition and enhancement effects. Liquid immersion model was proposed to describe flow regime and distribution of inlet header. Abstract: The aim of this study is to experimentally investigate the oil influences on transport, heat transfer and distribution performances of microchannel evaporator. Mixture of R32 and PVE VG68 oil was selected as the working fluid, and two single-pass microchannel heat exchangers were used as test samples. The experiments were conducted in mass flux range of 20–50 kg·m −2 ·s −1, nominal oil mass fraction (OMFno ) range of 0–6% and inlet local quality range of 0.1–0.16 at the saturation temperature of 12 °C. The result indicated that the oil retention volume ratio (ORVR) increases with the increments in oil mass fraction, inlet quality and decrease in mass flux. The upper outlet header tended to have remarkable oil retention and the oil transport behavior in header was analyzed. In most cases, the heat transfer was suppressed by the addition of oil. Heat transfer enhancement was observed at low oil mass fraction and high inlet quality conditions. The heat transfer factor ranged from 0.95 to 1.03, which indicated that the oil effect on heat transfer was not significant. Although the presence of oil inhibited the saturated boiling heat transfer coefficient, it could promote the heat transfer at superheat region. Struggle of inhibition and enhancement effects resulted in slight oil effect on heat transfer performance. An infrared-image-based distribution rating parameter was utilized to quantify the distribution performance. The oil effect on flow distribution was slight and the flow distribution deteriorated as the mass flux increased. A theoretical model called liquid immersion model was adopted to describe the flow regime and distribution mechanism in inlet header.